Comparison of various late gadolinium enhancement magnetic resonance imaging methods with high-definition voltage and activation mapping for detection of atrial cardiomyopathy. Issue 7 (17th March 2022) - Eichenlaub, Martin; Mueller-Edenborn, Bjoern; Minners, Jan; Figueras i Ventura, Rosa M; Forcada, Barbara Rubio; Colomer, Anna Vallès; Hein, Manuel; Ruile, Philipp; Lehrmann, Heiko; Schoechlin, Simon; Allgeier, Juergen; Bohnen, Marius; et al.
Abstract: Aims: Atrial cardiomyopathy (ACM) is associated with increased arrhythmia recurrence rates after pulmonary vein isolation (PVI). We compare the most common left atrial (LA) late gadolinium enhancement magnetic resonance imaging (LGE-MRI)-methods [Utah-method and image intensity ratio (IIR)-methods] and endocardial voltage mapping for ACM-detection and outcome prediction after PVI for atrial fibrillation (AF). Methods and results: In this prospective observational study, 37 ablation-naive patients (66 ± 9 years, 84% male) with persistent AF underwent LA-LGE-MRI and high-definition voltage and activation mapping (2129 ± 484 sites) in sinus rhythm prior to PVI. The MRI-post-processing-analyses were performed by two independent expert laboratories. Arrhythmia recurrence was recorded within 12 months following PVI. The global ACM-extent was highly variable: median LA low-voltage substrate (LA-LVS) was 12.9% at <1.0 mV and 2.7% at <0.5 mV; median LA-LGE-extent using the Utah-method was 18.3% and 0.03–93.1% using the IIR-methods. The LA activation time was significantly correlated with LA-LVS ( r = 0.76 at <0.5 mV and r = 0.82 at <1.0 mV, both P < 0.0001), but not with LA-LGE-extent. The highest regional matching between LA-LVS <0.5 mV and LA-LGE was found for the anterior wall in 57% of patients using the Utah-method and in 59% using IIR 1.20. The corresponding values for the posterior wall were 19% and 38%, respectively. Arrhythmia recurrence occurred in 15(41%) patients. Freedom from arrhythmia was significantly lower in those with LA-LVS ≥2 cm 2 at 0.5 mV but not in those with LGE ≥20% (Utah-stages III and IV): 43% vs. 81%, P = 0.009 and 50% vs. 67%, P = 0.338, respectively. Conclusion: Comparison of the most common LA-LGE-MRI methods and endocardial voltage mapping revealed large discrepancies in global and regional ACM-extent.